Towards evidence-based vitamin D supplementation in infants: vitamin D intervention in infants (VIDI) - study design and methods of a randomised controlled double-blinded intervention study - Otto Helve; Heli Viljakainen; Elisa Holmlund-Suila; Jenni Rosendahl; Helena Hauta-alus; Maria Enlund-Cerullo; Saara Valkama; Kati Heinonen; Katri Räikkönen; Timo Hytinantti; Outi Mäkitie; Sture Andersson (BMC, 2017)
Abstract Background Vitamin D is important for bone mass accrual during growth. Additionally, it is considered a requirement for a multitude of processes associated with, for example, the development of immunity. Many countries apply vitamin D supplementation strategies in infants, but the guidelines are not based on scientific evidence and aim at prevention of rickets. It remains unclear whether the recommended doses are sufficient for the wide array of other effects of vitamin D. The VIDI trial performed in Finland is the first large randomised controlled study for evaluation of the effects of different vitamin D supplemental doses in infancy on: 1. bone strength 2. infections and immunity 3. allergy, atopy and asthma 4. cognitive development 5. genetic regulation of mineral homeostasis Methods/Design VIDI, a randomised controlled double-blinded single-centre intervention study is conducted in infants from the age of 2 weeks to 24 months. Participants, recruited at Helsinki Maternity Hospital, are randomised to receive daily either 10 μg (400 IU) or 30 μg (1 200 IU) of vitamin D3 supplementation. Both groups are assessed at 6 months of age for calcium homeostasis, and at 12 and 24 months of age for parameters associated with bone strength, growth, developmental milestones, infections, immunity, atopy-related diseases, and genetic factors involved in these functions. Discussion The study enables evaluation of short and long term effects of supplemental vitamin D on growth, immune functions and skeletal and developmental parameters in infants, and the effects of genetic factors therein. The results enable institution of evidence-based guidelines for vitamin D supplementation in infancy. Trial registration ClinicalTrials.gov, NCT01723852 , registration date 6.11.2012.